Assessment of groundwater quality contamination by nitrate leaching using multivariate statistics and Geographic Information Systems. - Matiatos, I.; Evelpidou, N. (IAHS-AISH Proceedings and Reports, 2013)
The present study examines nitrate contamination and groundwater quality in the Megara basin of Attica Prefecture (Greece). Hydrochemical data were assessed using descriptive and multivariate statistical analysis to (1) classify the data into hydrochemically similar groups, and (2) to investigate geochemical and human-related factors responsible for the observed groundwater quality. Geographic Information Systems (GIS) were used to incorporate both thematic (landuse) data and groundwater chemistry to study the extent and variation of nitrate contamination and to establish spatial relationships with specific landuse types. The results indicate that more than 70% of the groundwater samples located around the national highway had nitrate concentrations that exceeded acceptable levels according to international legislation and guidelines (Directive 98/83/EC, EPA, WHO). The combined spatial analysis and statistical hydrochemical evaluation show that nitrate contamination in groundwater is closely associated with specific landuse classes and activities (e.g. agriculture, pasture, industries, urban effluents).